Adsorbing material for adsorbing pterocarya stenoptera essential oil as well as preparation method and application of adsorbing material

A multi-layered adsorption material with molecular recognition cores selectively adsorbs maple poplar essential oil, addressing the lack of selectivity in existing magnetic materials and enhancing adsorption efficiency.

CN119186516APending Publication Date: 2024-12-27HONGHU LANTIAN ANHUAN ENERGY SAVING EQUIP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411317244.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing magnetic materials lack selectivity in adsorbing maple poplar essential oil, adsorbing all molecules indiscriminately due to similar hydrophilic and hydrophobic properties.

Method used

An adsorption material is prepared using halloysite powder, Fe(NO3)3·9H2O, silanization agent, imidazole modifier, triethylamine, maple elm essential oil, Zn(NO3)2·6H2O, and dichloroalkane, forming a multi-layered structure with molecular recognition cores to selectively adsorb maple poplar essential oil through electrostatic and hydrophobic forces.

Benefits of technology

The material achieves high selective adsorption and separation of maple poplar essential oil from solutions, improving utilization rates and enabling efficient concentration of plant essential oils.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186516A_ABST
    Figure CN119186516A_ABST
Patent Text Reader

Abstract

The invention discloses an adsorption material for adsorbing pterocarya stenoptera essential oil and a preparation method and application thereof, and belongs to the technical field of adsorption materials, the adsorption material for adsorbing the pterocarya stenoptera essential oil comprises the following raw materials: halloysite powder, Fe (NO3) 3.9 H2O, an imidazole modifier, triethylamine, the pterocarya stenoptera essential oil, Zn (NO3) 2.6 H2O and the like. The preparation method comprises the following steps: mixing magnetic halloysite and a silanization reagent, and then mixing the mixture with an imidazole modifier, pterocarya stenoptera essential oil 1 and the like to obtain Im-MHNT; the preparation method comprises the following steps: dissolving the Im-MHNT and Zn (NO3) 2.6 H2O to obtain ZIF67-MHNT; the preparation method comprises the following steps: mixing an imidazole modifier and dichloroalkane to obtain Cl-IL; putting the ZIF67-MHNT, the Cl-IL and the pterocarya stenoptera essential oil 2 into xylene, uniformly mixing, and heating to obtain the adsorption material. The adsorption material disclosed by the invention has high selective adsorbability and adsorbability on the pterocarya stenoptera essential oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption materials, and in particular to an adsorption material for adsorbing maple poplar essential oil and a preparation method and application thereof. Background Art

[0002] Maple poplar essential oil contains a large amount of volatile substances such as sterols, guaiaretic acid, and bisabolene. The common chemical structure of these volatile substances is that they contain benzene rings and long-chain alkane structures, with a molecular weight between 200-400. They have good antibacterial and antioxidant properties and have certain medicinal value.

[0003] Steam distillation is one of the common methods for preparing euphorbia obesa essential oil. At present, steam distillation is the most widely used method, with simple equipment, convenient operation, no solvent residue, low cost, easy promotion, strong practicality, good stability, and relatively mature technology, equipment and operation. After the euphorbia obesa leaves are steam distilled, the euphorbia obesa essential oil will be distilled out along with the water vapor, and after condensation, the euphorbia obesa essential oil can be obtained by separating the oil and water phases. However, the condensate obtained after condensation is mainly composed of water, and the amount of euphorbia obesa essential oil is far less than that of water. A small amount of essential oil droplets are suspended in the condensate to form oil droplets with a particle size of less than 0.1 microns. Because of its increased solubility in water, it cannot be used by the oil-water separation method.

[0004] In order to recover a small amount of essential oil in water, one method is to use adsorbent materials to adsorb essential oil molecules. Among the existing adsorbent materials, magnetic nano-adsorbent materials have attracted widespread attention due to their large specific surface area, high adsorption performance and unique magnetic separation method. The magnetic separation method uses nano-magnetic particles as adsorbent material carriers, and after adsorbing the target molecules, it uses the directional control of the external magnetic field to quickly separate the target molecules in the mixed system.

[0005] At present, the main magnetic materials are metal oxides Fe2O3, MFe2O4 (M=Co, Mn, Ni) and Fe3O4, etc., but these magnetic materials have no selectivity in the adsorption of maple essential oil. They just adsorb all molecules indiscriminately by relying on the similar hydrophilic and hydrophobic properties between molecules. Summary of the invention

[0006] The purpose of the present invention is to overcome the above technical deficiencies and provide an adsorption material for adsorbing maple poplar essential oil and a preparation method and application thereof, so as to solve the technical problem that magnetic materials in the prior art have no selectivity in adsorbing maple poplar essential oil.

[0007] In order to achieve the above technical purpose, the technical solution of the present invention provides an adsorption material for adsorbing maple elm essential oil, and its raw materials include the following components: halloysite powder, Fe(NO3)3·9H2O, silanization agent, imidazole modifier, triethylamine, maple elm essential oil, Zn(NO3)2·6H2O, and dichloroalkane.

[0008] Preferably, the silanization agent is one of chloromethyltrimethoxysilane, chloropropyltrimethoxysilane, chloropropyltriethoxysilane and bromopropyltrimethoxysilane.

[0009] Preferably, the imidazole modifier is one of imidazole, ethyl imidazole and propyl imidazole.

[0010] A method for preparing an adsorption material for adsorbing maple essential oil as described above comprises the following steps:

[0011] S1, mixing halloysite powder, Fe(NO3)3·9H2O and anhydrous ethanol, heating to 320-550°C at a heating rate of 5-20°C per minute under a nitrogen atmosphere, and keeping the temperature for 2 hours to obtain magnetic halloysite, which is recorded as MHNT;

[0012] S2, the MHNT, silanization agent and xylene are mixed evenly, heated to 90° C. and stirred for 8 hours to obtain a white powder, the white powder is mixed evenly with an imidazole modifier, triethylamine, maple essential oil 1 and xylene, heated to 100° C. and stirred for 6 hours to obtain imidazole group-modified magnetic halloysite, which is recorded as Im-MHNT;

[0013] S3, dissolving the Im-MHNT and Zn(NO3)2·6H2O in methanol, stirring for 30 minutes and then standing to obtain metal organic framework modified magnetic halloysite, recorded as ZIF67-MHNT;

[0014] S4, placing an imidazole modifier and a dichloroalkane in xylene and mixing them evenly, heating to 80°C and stirring continuously for 2 hours to obtain a chloroimidazole ionic liquid, recorded as Cl-IL;

[0015] S5. Put the ZIF67-MHNT, the Cl-IL and the red poplar essential oil 2 into xylene and mix them evenly. Heat to 80° C. and continue stirring for 6 hours to obtain an adsorption material for adsorbing the red poplar essential oil, which is recorded as IL-ZIF67-MHNT.

[0016] Preferably, the mass ratio of the halloysite powder to Fe(NO3)3·9H2O in S1 is 1:0.1-10.

[0017] Preferably, the mass ratio of MHNT, silanization agent, imidazole modifier, triethylamine and maple essential oil 1 in S2 is 1:1-5:2-7:0.2-1:2-7.

[0018] Preferably, the mass ratio of Im-MHNT, Zn(NO3)2·6H2O and methanol in S3 is 1:0.2-2:30-80.

[0019] Preferably, the mass ratio of the imidazole modifier and the dichloroalkane in S4 is 1:0.5-3, and the dichloroalkane is one of 1,4-dichlorobutane, 1,6-dichlorohexane and 1,9-dichlorononane.

[0020] Preferably, the mass ratio of ZIF67-MHNT, Cl-IL and Acer truncatum essential oil 2 in S5 is 1:0.17-0.95:1-10.

[0021] An application of the adsorption material described above in adsorbing maple poplar essential oil.

[0022] The ionic liquid-metal organic framework-magnetic halloysite adsorption material prepared by the patent of the present invention takes the hydrophobic maple poplar essential oil as the molecular recognition core, and utilizes the anions and cations, alkyl chains, imidazole rings, nitrogen atoms on the ionic liquid and the hydroxyl groups, carbonyl groups, alkyl chains, carbon rings and unsaturated bonds in the maple poplar essential oil molecules to generate electrostatic forces, hydrogen bonding forces, π-π bonding forces, and hydrophobic forces; utilizes the zinc ions, imidazole rings and their side chains on the metal organic framework and the unsaturated bonds, hydroxyl groups, carbonyl groups, and alkyl chains in the maple poplar essential oil molecules to generate electrostatic forces, π-π bonding forces, and hydrophobic forces, reflecting the adsorption capacity of the maple poplar essential oil molecules.

[0023] The adsorption material of the present invention is an ionic liquid-metal organic framework-magnetic halloysite adsorption material. In the preparation process, a silanization agent is first used to modify the magnetic halloysite to form a first coating on the magnetic halloysite; then an imidazole modifier is used to modify it again to form a second coating. In the process of forming the second coating, the maple poplar essential oil is used for the first time. The purpose is to utilize the molecular structure size, functional group type (hydroxyl, carbonyl, alkyl chain, carbon ring and unsaturated bond) and functional group arrangement order of the maple poplar essential oil to promote the imidazole groups to be arranged in a specific order through hydrogen bonding forces, π-π bonding forces and hydrophobic forces during the reaction to prepare Im-MHNT; the maple poplar essential oil molecules in the second coating process promote the imidazole groups to be arranged in a specific order, and the specific order arrangement can produce intermolecular forces in a specific direction during the adsorption process, which is beneficial to improve the selective adsorption capacity of the maple poplar essential oil molecules;

[0024] Then, in step S3, the specific sequence arrangement and steric hindrance of the imidazole groups are utilized to coat ZIF67 on the outside to form a third coating layer;

[0025] 1) ZIF67-MHNT has a rich pore structure with a pore size of about 1.1nm, while the size of the maple poplar essential oil molecule is about 0.8nm, which is just suitable for accommodating the maple poplar essential oil molecules. The maple poplar essential oil molecules can be fully embedded in the ZIF67 pores, and the molecular structure size can be used to improve the selectivity while having a high adsorption capacity;

[0026] 2) ZIF67-MHNT is prepared by coordination assembly of imidazole rings and Zn atoms. The imidazole rings on ZIF67-MHNT can form ionic liquids with dichloroalkanes through chemical reactions, and the functional groups of the ionic liquids can be structurally adjusted according to the molecular size and functional groups (hydroxyl, carbonyl, alkyl chain, carbon ring and unsaturated bond) of the essential oil to enhance the adsorption amount and selectivity of the essential oil molecules.

[0027] In S4, suitable imidazole modifiers and dichloroalkanes were selected based on the chemical structure of maple poplar essential oil; in S5, maple poplar essential oil was used again in the process of modifying the ionic liquid. The purpose was to utilize the molecular structure size, functional group type (hydroxyl, carbonyl, alkyl chain, carbon ring and unsaturated bond) and functional group arrangement order of maple poplar essential oil, and in the process of preparing the outermost ionic liquid functional groups by reaction, the ionic bond force, hydrogen bond force, π-π bond force and hydrophobic force caused the ionic liquid functional groups to be arranged in a specific order to form the fourth layer of coating.

[0028] During the fourth layer coating process, the maple poplar essential oil molecules cause the ionic liquid functional groups to arrange in a specific order, and together with the inner ZIF67, they produce intermolecular forces in a specific direction on the maple poplar essential oil molecules, which is beneficial to improving the selective adsorption capacity of the maple poplar essential oil molecules.

[0029] Compared with the prior art, the beneficial effects of the present invention include:

[0030] The invention utilizes the molecular imprinting principle, takes halloysite with high specific surface area as a magnetic matrix, uses eucalyptus essential oil as a template molecule, and uses a metal organic framework and an ionic liquid as a molecular recognition core to prepare a magnetic adsorption material with good adsorption performance and capable of identifying eucalyptus essential oil molecules.

[0031] Acer truncatum essential oil contains a large amount of chemical substances such as sterols, guaiaretic acid, and bisabolene, which contain chemical bonds such as long-chain alkyls, hydroxyls, and carbonyls. The functional groups on the metal-organic framework and ionic liquids can form specific chemical forces with the Acer truncatum essential oil molecules through hydrophilic / hydrophobic, hydrogen bonds, π-π bonds, ionic bonds and other chemical bonds, thereby being able to well identify the Acer truncatum essential oil molecules during the adsorption process.

[0032] Halloysite has a hollow nanotube structure with two ends open. It is a nanomaterial with a large specific surface area and high thermal stability. It can cover the magnetic center on the inner and outer surfaces of the nanotube structure. In the process of preparing the adsorption material, imidazole modifiers are used step by step to form ionic liquid modification layers on the inside and outside of ZIF67; the addition of maple poplar essential oil twice increases the number of molecular recognition cores and improves the adsorption material's ability to recognize maple poplar essential oil molecules.

[0033] The ionic liquid-metal organic framework-magnetic halloysite adsorption material of the present invention has high selective adsorption for the maple poplar essential oil, and after adsorption, the maple poplar essential oil molecules can be well separated from the solution by using a magnetic field. The adsorption material of the present invention can also be used to adsorb and concentrate specific plant essential oils in a low-concentration environment, improve the utilization rate of the plant essential oils, and has good application prospects in loading plant essential oils. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a field transmission electron microscopy image of the adsorption material prepared in Example 4;

[0035] Figure 2 is a scanning electron microscope image of the magnetic halloysite prepared in Example 4;

[0036] Figure 3 is a scanning electron micrograph of IL-ZIF67-MHNT prepared in Example 4;

[0037] Figure 4 is the Fourier infrared spectrum of the adsorption material prepared in Example 4;

[0038] Figure 5 is a thermogravimetric analysis diagram of the adsorption material prepared in Example 4;

[0039] Figure 6 This is a magnetic field response measurement diagram of the adsorption material prepared in Example 4;

[0040] Figure 7 is another magnetic field response measurement diagram of the adsorption material prepared in Example 4;

[0041] Figure 8 This is a test chart of the adsorption amount of maple essential oil by the adsorption materials prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 3;

[0042] Fig. 9 This is a test chart of the adsorption amount of the adsorption material prepared in Example 4 at different concentrations of maple poplar essential oil;

[0043] Fig.10 This is a test chart of the adsorption amount of maple essential oil by the adsorption material prepared in Example 4 at different temperatures. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0045] This specific implementation provides a kind of.

[0046] Example 1

[0047] This embodiment provides an adsorption material for adsorbing maple poplar essential oil, and its raw materials include the following components: halloysite powder, Fe(NO3)3·9H2O, silanization agent, imidazole modifier, triethylamine, maple poplar essential oil 1, Zn(NO3)2·6H2O, and dichloroalkane.

[0048] This embodiment also provides a method for preparing an adsorption material for adsorbing maple essential oil, comprising the following steps:

[0049] (1) 2 g of halloysite powder, 0.2 g of Fe(NO3)3·9H2O and 30 g of anhydrous ethanol were mixed in a conical flask and stirred at room temperature for 6 h. Subsequently, the mixture was placed in a tubular furnace under a nitrogen atmosphere and heated to 320°C at a heating rate of 5°C per minute and maintained for 2 h to obtain 2.2 g of MHNT.

[0050] (2) The obtained 2.2 g MHNT, 2.2 g chloromethyltrimethoxysilane and 6.6 g xylene were placed in a round-bottom flask and mixed evenly, heated to 90°C and stirred for 8 hours to obtain 4.4 g white powder; the obtained 4.4 g white powder, 4.4 g imidazole, 0.44 g triethylamine, 4.4 g maple essential oil and 6.6 g xylene were placed in a round-bottom flask and mixed evenly, heated to 100°C and stirred for 6 hours to obtain 8.2 g Im-MHNT.

[0051] (3) The obtained 8.2 g of Im-MHNT and 1.64 g of Zn(NO3)2·6H2O were dissolved in 246 g of methanol, stirred for 30 minutes and then allowed to stand at room temperature for 15 hours to obtain 9.5 g of ZIF67-MHNT.

[0052] (4) 5 g of imidazole and 2.5 g of 1,4-dichlorobutane were mixed in 250 g of xylene, heated to 80 °C and stirred for 2 hours to obtain 7.3 g of Cl-IL.

[0053] (5) 9.5 g of the obtained ZIF67-MHNT, 7.3 g of the obtained Cl-IL and 18 g of the maple essential oil were mixed in 250 g of xylene, heated to 80° C. and stirred for 6 hours to obtain 16 g of IL-ZIF67-MHNT.

[0054] Example 2

[0055] This embodiment provides an adsorption material for adsorbing maple poplar essential oil, and its raw materials include the following components: halloysite powder, Fe(NO3)3·9H2O, silanization agent, imidazole modifier, triethylamine, maple poplar essential oil 1, Zn(NO3)2·6H2O, and dichloroalkane.

[0056] This embodiment also provides a method for preparing an adsorption material for adsorbing maple essential oil, comprising the following steps:

[0057] (1) 5 g of halloysite powder, 50 g of Fe(NO3)3·9H2O and 200 g of anhydrous ethanol were mixed in a conical flask and stirred at room temperature for 12 h. Subsequently, the mixture was placed in a tubular furnace under a nitrogen atmosphere and heated to 550°C at a heating rate of 20°C per minute and maintained for 2 h to obtain 55 g of MHNT.

[0058] (2) 55 g of MHNT, 275 g of chloropropyltriethoxysilane and 825 g of xylene were placed in a round-bottom flask and mixed evenly. The mixture was heated to 90° C. and stirred for 8 hours to obtain 320 g of white powder. The 320 g of white powder was mixed with 385 g of ethylimidazole, 55 g of triethylamine, 385 g of maple essential oil and 825 g of xylene in a round-bottom flask. The mixture was heated to 100° C. and stirred for 6 hours to obtain 700 g of Im-MHNT.

[0059] (3) 700 g of the obtained Im-MHNT and 1400 g of Zn(NO3)2·6H2O were dissolved in 56 kg of methanol, stirred for 30 minutes and then allowed to stand at room temperature for 36 hours to obtain 2000 g of ZIF67-MHNT.

[0060] (4) 500 g of ethylimidazole and 1500 g of 1,9-dichlorononane were mixed in 250 g of xylene, heated to 80°C and stirred for 2 hours to obtain 1830 g of Cl-IL.

[0061] (5) 2000 g of the obtained ZIF67-MHNT, 1830 g of the obtained Cl-IL and 20000 g of the essential oil of maple poplar were mixed in 250 g of xylene, heated to 80° C. and stirred for 6 hours to obtain 3814 g of IL-ZIF67-MHNT.

[0062] Example 3

[0063] This embodiment provides an adsorption material for adsorbing maple poplar essential oil, and its raw materials include the following components: halloysite powder, Fe(NO3)3·9H2O, silanization agent, imidazole modifier, triethylamine, maple poplar essential oil 1, Zn(NO3)2·6H2O, and dichloroalkane.

[0064] This embodiment also provides a method for preparing an adsorption material for adsorbing maple essential oil, comprising the following steps:

[0065] (1) 2 g of halloysite powder, 16 g of Fe(NO3)3·9H2O and 100 g of anhydrous ethanol were mixed in a conical flask and stirred at room temperature for 10 h. Subsequently, the mixture was placed in a tubular furnace under a nitrogen atmosphere and heated to 400°C at a heating rate of 10°C per minute and maintained for 2 h to obtain 17 g of MHNT.

[0066] (2) The obtained 17 g MHNT, 68 g bromopropyltrimethoxysilane and 250 g xylene were placed in a round-bottom flask and mixed evenly, heated to 90°C and stirred for 8 hours to obtain 83 g white powder; the obtained 83 g white powder, 65 g propylimidazole, 10 g triethylamine, 50 g maple essential oil and 250 g xylene were placed in a round-bottom flask and mixed evenly, heated to 100°C and stirred for 6 hours to obtain 140 g Im-MHNT.

[0067] (3) 140 g of the obtained Im-MHNT and 140 g of Zn(NO3)2·6H2O were dissolved in 500 g of methanol, stirred for 30 minutes and then allowed to stand at room temperature for 24 hours to obtain 270 g of ZIF67-MHNT.

[0068] (4) 50 g of propyl imidazole and 100 g of 1,6-dichlorohexane were mixed in 250 g of xylene, heated to 80°C and stirred for 2 hours to obtain 142 g of Cl-IL.

[0069] (5) 270 g of the obtained ZIF67-MHNT, 142 g of the obtained Cl-IL and 500 g of the essential oil of maple poplar were mixed in 250 g of xylene, heated to 80° C. and stirred for 6 hours to obtain 400 g of IL-ZIF67-MHNT.

[0070] Example 4

[0071] This embodiment provides an adsorption material for adsorbing maple poplar essential oil, and its raw materials include the following components: halloysite powder, Fe(NO3)3·9H2O, silanization agent, imidazole modifier, triethylamine, maple poplar essential oil 1, Zn(NO3)2·6H2O, and dichloroalkane.

[0072] This embodiment also provides a method for preparing an adsorption material for adsorbing maple essential oil, comprising the following steps:

[0073] (1) 2 g of halloysite powder, 5 g of Fe(NO3)3·9H2O and 200 g of anhydrous ethanol were mixed in a conical flask and stirred at room temperature for 8 h. Subsequently, the mixture was placed in a tubular furnace under a nitrogen atmosphere and heated to 350°C at a heating rate of 5°C per minute and maintained for 2 h to obtain 7 g of MHNT.

[0074] (2) 7 g of MHNT, 15 g of chloropropyltrimethoxysilane and 300 g of xylene were placed in a round-bottom flask and mixed evenly. The mixture was heated to 90° C. and stirred for 8 hours to obtain 21 g of white powder. The 21 g of white powder was mixed with 60 g of propylimidazole, 15 g of triethylamine, 60 g of maple essential oil and 300 g of xylene in a round-bottom flask and mixed evenly. The mixture was heated to 100° C. and stirred for 6 hours to obtain 80 g of Im-MHNT.

[0075] (3) 80 g of the obtained Im-MHNT and 85 g of Zn(NO3)2·6H2O were dissolved in 400 g of methanol, stirred for 30 minutes and then allowed to stand at room temperature for 36 hours to obtain 160 g of ZIF67-MHNT.

[0076] (4) 10 g of propyl imidazole and 18 g of 1,6-dichlorohexane were mixed in 250 g of xylene, heated to 80°C and stirred for 2 hours to obtain 27 g of Cl-IL.

[0077] (5) 160 g of the obtained ZIF67-MHNT, 27 g of the obtained Cl-IL and 165 g of the maple essential oil were mixed in 250 g of xylene, heated to 80° C. and stirred for 6 hours to obtain 184 g of IL-ZIF67-MHNT.

[0078] The following properties were measured for the adsorption material for adsorbing maple poplar essential oil prepared in Example 4:

[0079] 1. Field transmission electron microscopy analysis

[0080] The equipment used for field transmission electron microscopy measurement was a transmission electron microscope Tecnai G2 F20S-TWIN (FEI, USA). Figure 1 , is a field transmission electron microscopy image of the adsorption material prepared in Example 4, Figure 1 The hollow tubular structure of halloysite is shown, and the black nano-magnetic particles are clearly loaded on the inner and outer walls of the halloysite nanotubes, with an average particle size of 10-20 nm. Therefore, the field transmission electron microscopy analysis shows that the magnetic halloysite material of the present invention is successfully prepared.

[0081] 2. Scanning electron microscopy measurement

[0082] The scanning electron microscope was used for the measurement with MIRA3 (Tesken, Czech Republic). Figure 2 is the SEM image of the magnetic halloysite in step (1), Figure 3 This is a SEM image of IL-ZIF67-MHNT (ionic liquid-metal organic framework-magnetic halloysite adsorption material) in step (5), showing the material morphology before and after the ionic liquid-metal organic framework modified the magnetic halloysite. Figure 2The image in the figure shows the unmodified morphology of magnetic halloysite, and it can be seen that the outer surface of the halloysite nanotube is smooth; Figure 3 The morphology of the magnetic halloysite after being modified by the ionic liquid-metal organic framework is shown in FIG. 1 , and it can be seen that a rough ionic liquid-metal organic framework coating layer has been formed on the outer surface of the halloysite nanotube. Therefore, the scanning electron microscope data shows that the ionic liquid-metal organic framework-magnetic halloysite adsorption material of the present invention is successfully prepared.

[0083] 3. Fourier transform infrared spectroscopy

[0084] The instrument used for Fourier transform infrared spectroscopy was Nicolet 6700 (Thermo Fisher Scientific, USA). Figure 4 Medium, 3695cm -1 and 3623cm -1 The two characteristic peaks at 3448 cm are the stretching vibration peaks of Al-OH on halloysite. -1 The characteristic peak at 1645 cm is the CH vibration peak of imidazole. -1 C=C stretching vibration peak, 1400cm -1 The CN stretching vibration peak of the imidazole ring in ionic liquids and metal organic frameworks; 1096 cm -1 The Si-O stretching vibration absorption is 1034 cm -1 It is the Si-O-Si stretching vibration absorption peak, 536cm -1 It is the deformation vibration of Al-O-Si. -1 and 469cm -1 = and , respectively, represent the inner surface hydroxyl vibration and Si-O-Si stretching vibration. Therefore, the Fourier transform infrared spectroscopy analysis data shows that the ionic liquid-metal organic framework-magnetic halloysite adsorption material in this embodiment is successfully prepared.

[0085] 4. Thermogravimetric analysis

[0086] Thermogravimetric analysis was performed using Labsys evo (Setaram, France). Figure 5 The results show that the ionic liquid-metal organic framework-magnetic halloysite adsorbent (IL-ZIF67-MHNT) of this embodiment loses 42.8% of its mass within 500°C, which is caused by the decomposition of the ionic liquid functional groups at high temperatures; and loses 16.5% of its mass between 500°C and 700°C, which is caused by the decomposition of the metal organic framework at high temperatures. Therefore, the thermogravimetric analysis data shows that the ionic liquid-metal organic framework-magnetic halloysite adsorbent of this embodiment is successfully prepared and has a complex coating structure.

[0087] 5. Magnetic field response measurement

[0088] Figure 6 , Figure 7 The responsiveness of the ionic liquid-metal organic framework-magnetic halloysite adsorption material (IL-ZIF67-MHNT) prepared in this example to a magnetic field is shown; Figure 6 It shows that the adsorbed material is dispersed in the solution system when no magnetic field is applied; Figure 7 It is shown that the adsorbed material is gathered on one side of the magnet in the presence of a magnet. Therefore, it is shown that the ionic liquid-metal organic framework-magnetic halloysite adsorbent material is successfully prepared.

[0089] The relevant test results of the adsorption materials obtained in Examples 1-3 are similar to those in Example 4.

[0090] Comparative Example 1

[0091] This comparative example is the same as Example 4, except that no maple poplar essential oil is added in step (2) of this comparative example.

[0092] Comparative Example 2

[0093] This comparative example is the same as Example 4, except that no maple poplar essential oil is added in step (5) of this comparative example.

[0094] Comparative Example 3

[0095] This comparative example is the same as Example 4, except that in this comparative example, no maple poplar essential oil is added in step (2) and step (5).

[0096] Comparative Example 4

[0097] This comparative example is the same as Example 4, except that, in this comparative example, step (3) is cancelled, and in step (5), "160 g of ZIF67-MHNT obtained" is changed to "80 g of Im-MHNT".

[0098] In order to further illustrate the effect of the adsorption material of the present invention on the adsorption of Acer truncatum essential oil, the following measurements were performed.

[0099] The adsorption materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were used to measure the adsorption amount of the essential oil of Pteris crenata.

[0100] 10 ml of Acer truncatum essential oil was placed in 7 conical flasks, and 1 gram of the adsorption material prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was added respectively; the conical flasks were shaken for 1 minute and allowed to stand for 20 minutes, then the adsorption material was taken out with a magnet, and the concentration of Acer truncatum essential oil before and after adsorption was determined by liquid chromatography.

[0101] The concentration of maple poplar essential oil was determined under the same liquid chromatography conditions. The liquid chromatography detection conditions were: LC3000 (CXTH, China), TC-C18 column (4.6×150mm, 5μm, Agilent, USA), mobile phase methanol / water (85:15, v / v), flow rate 0.8mL / min, UV detector wavelength 470nm, column temperature 30℃. The concentration of maple poplar essential oil was calculated by the sum of peak areas.

[0102] The adsorption amount of maple essential oil was calculated by formula (1):

[0103]

[0104] Where q e is the adsorption amount of maple essential oil when the adsorption reaches equilibrium, in mg / g; C0 is the solution concentration before adsorption, in mg / mL; C e is the concentration of the solution at adsorption equilibrium, in mg / mL; V is the volume of the solution, in mL; m is the mass of the adsorbent material, in g.

[0105] The adsorption data of maple poplar essential oil obtained by the adsorption materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 are as follows Figure 8 As shown. The adsorption materials prepared in Examples 1 to 4 have a higher adsorption capacity for Acer truncatum essential oil because the template molecules and the molecular recognition core raw materials are added in sequence. For Comparative Example 1, a molecular recognition core cannot be formed between the inner side of ZIF67 and the ionic liquid functional groups due to the lack of template molecules, while a partial molecular recognition core is formed between the outer side of ZIF67 and the ionic liquid functional groups, so the adsorption capacity of Acer truncatum essential oil is reduced. For Comparative Example 2, a molecular recognition core is formed between the inner side of ZIF67 and the ionic liquid functional groups, but is wrapped by other functional groups on the outside, resulting in the molecular recognition core being unable to fully contact the Acer truncatum essential oil molecules, resulting in a further decrease in the adsorption capacity. For Comparative Example 3, since no molecular recognition core can be formed during its preparation process, the adsorption capacity is the lowest.

[0106] The experimental results show that the ionic liquid-metal organic framework-magnetic halloysite adsorption materials in Examples 1 to 4 have a good adsorption effect on the essential oil of Acer truncatum.

[0107] In order to further illustrate the adsorption effect of the ionic liquid-metal organic framework-magnetic halloysite adsorption material (IL-ZIF67-MHNT) of the present invention on the essential oil of maple poplar under different external environments, the following tests were performed.

[0108] Different concentrations of maple essential oil were placed in conical flasks, and 1 gram of the adsorption material prepared in Example 4 was added to each flask; the conical flask was shaken at room temperature for 1 minute and allowed to stand for 20 minutes, then the adsorption material was taken out with a magnet, and the concentration of maple essential oil before and after adsorption was determined by liquid chromatography.

[0109] The liquid chromatography detection conditions and adsorption amount calculation equation refer to formula (1).

[0110] Fig. 9 The data graph of the adsorption amount of the ionic liquid-metal organic framework modified magnetic halloysite adsorbent (IL-ZIF67-MHNT) prepared in Example 4 at different concentrations of maple poplar essential oil is shown. It can be seen that as the initial concentration increases, the adsorption amount increases accordingly, and the adsorption amount does not increase after reaching the maximum. This shows that the ionic liquid-metal organic framework modified magnetic halloysite adsorbent (IL-ZIF67-MHNT) of this example has a high adsorption efficiency for low concentrations of maple poplar essential oil.

[0111] The same concentration of maple essential oil was placed in conical flasks, and 1 gram of the adsorption material prepared in Example 4 was added to each of them; the conical flasks were shaken for 1 minute, and adsorption was carried out at 10° C. for 20 minutes. The adsorption material was then taken out with a magnet, and the concentration of maple essential oil before and after adsorption at this temperature was determined by liquid chromatography.

[0112] The adsorption temperature was changed to 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C and 70°C, and the adsorption effect of the adsorption material prepared in Example 4 on maple poplar essential oil at different temperatures was measured.

[0113] The liquid chromatography detection conditions and adsorption amount calculation equation refer to formula (1).

[0114] Fig.10 The data graph of the adsorption amount of the ionic liquid-metal organic framework modified magnetic halloysite adsorbent (IL-ZIF67-MHNT) of the embodiment for the maple poplar essential oil at different temperatures is shown. It can be seen that as the temperature rises, the adsorption amount also increases. However, when the temperature exceeds 40°C, the trend of desorption of the essential oil molecules from the adsorbent material increases, resulting in a significant decrease in the adsorption amount. It shows that the ionic liquid-metal organic framework modified magnetic halloysite adsorbent (IL-ZIF67-MHNT) of this embodiment has a high adsorption efficiency for the maple poplar essential oil in the range of 20°C-40°C.

[0115] In order to further illustrate the effect of the adsorption material of the present invention on the adsorption selectivity of maple poplar essential oil, we conducted the following tests.

[0116] After placing 10 mL of maple essential oil, orange peel essential oil, clove essential oil, lemon essential oil and pine needle essential oil of the same concentration in 5 conical flasks, 1 gram of the adsorption material prepared in Example 4 was added to each of the flasks; the conical flasks were shaken at room temperature for 1 minute and allowed to stand for 20 minutes, and then the adsorption material was taken out with a magnet, and the concentration of maple essential oil before and after adsorption was measured by liquid chromatography;

[0117] 10 mL of maple essential oil, orange peel essential oil, clove essential oil, lemon essential oil and pine needle essential oil of the same concentration were placed in 5 conical flasks respectively, and then 1 gram of the adsorption material prepared in Comparative Example 3 was added respectively; the conical flasks were shaken at room temperature for 1 minute and allowed to stand for 20 minutes, and then the adsorption material was taken out with a magnet, and the concentration of maple essential oil before and after adsorption was determined by liquid chromatography;

[0118] 10 mL of maple essential oil, orange peel essential oil, clove essential oil, lemon essential oil and pine needle essential oil of the same concentration were placed in 5 conical flasks respectively, and then 1 gram of the adsorption material prepared in Comparative Example 4 was added respectively; the conical flask was shaken at room temperature for 1 minute and allowed to stand for 20 minutes, then the adsorption material was taken out with a magnet, and the concentration of maple essential oil before and after adsorption was determined by liquid chromatography.

[0119] The liquid chromatography detection conditions and the adsorption amount calculation equation refer to formula (1), and the measurement results are shown in Table 1.

[0120] Table 1 Adsorption amount of different plant essential oils by different adsorption materials

[0121]

[0122] The adsorption material prepared in Example 4 has the highest adsorption capacity for maple poplar essential oil because the template molecule and the molecular recognition core raw material are added in sequence. Pine needle essential oil contains volatile substances with chemical structures similar to sterols and guaiaretic acid, so the adsorption capacity of the adsorption material for it is slightly higher than that of orange peel essential oil, clove essential oil and lemon essential oil.

[0123] The adsorption material prepared in Comparative Example 3 did not add template molecules, so the arrangement of ionic liquid and metal organic framework functional groups during the preparation process could not form a molecular recognition core, and the adsorption of maple poplar essential oil was the lowest. However, because it contained a large specific surface area and hydrophobic long-chain alkanes, it had a certain non-selective adsorption of other plant essential oils.

[0124] The adsorption material prepared in Comparative Example 4 eliminated step (3) and directly reacted Im-MHNT with Cl-IL to obtain a diionic liquid modified magnetic halloysite adsorption material. During the preparation process, the maple poplar essential oil was used twice, so that the arrangement of the ionic liquid functional groups had the ability to partially recognize molecules, and the selectivity for the maple poplar essential oil was significantly higher than that for other essential oil molecules. However, its surface was not coated with the ZIF66 metal organic framework structure, resulting in a significant reduction in the number of pores and specific surface area, so the adsorption amount of the maple poplar essential oil molecules was small.

[0125] The experimental results show that the ionic liquid-metal organic framework-magnetic halloysite adsorption material of the present invention has good selectivity for maple poplar essential oil.

[0126] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. An adsorption material for adsorbing maple poplar essential oil, characterized in that: Its raw materials Includes the following components: Halloysite powder, Fe(NO3)3·9H2O, silanization reagent, imidazole modifier, triethylamine, maple essential oil, Zn(NO3)2·6H2O, dichloroalkane.

2. The adsorption material for adsorbing maple poplar essential oil according to claim 1, characterized in that: The silanization agent is one of chloromethyltrimethoxysilane, chloropropyltrimethoxysilane, chloropropyltriethoxysilane and bromopropyltrimethoxysilane.

3. The adsorption material for adsorbing maple poplar essential oil according to claim 1, characterized in that: The imidazole modifier is one of imidazole, ethyl imidazole and propyl imidazole.

4. A method for preparing an adsorption material for adsorbing maple essential oil according to any one of claims 1 to 3, characterized in that: The steps include: S1, mixing halloysite powder, Fe(NO3)3·9H2O and anhydrous ethanol, heating to 320-550°C at a heating rate of 5-20°C per minute under a nitrogen atmosphere, and keeping the temperature for 2 hours to obtain magnetic halloysite, which is recorded as MHNT; S2, the MHNT, silanization agent and xylene are mixed evenly, heated to 90° C. and stirred for 8 hours to obtain a white powder, the white powder is mixed evenly with an imidazole modifier, triethylamine, maple essential oil 1 and xylene, heated to 100° C. and stirred for 6 hours to obtain imidazole group-modified magnetic halloysite, which is recorded as Im-MHNT; S3, dissolving the Im-MHNT and Zn(NO3)2·6H2O in methanol, stirring for 30 minutes and then standing to obtain metal organic framework modified magnetic halloysite, recorded as ZIF67-MHNT; S4, placing an imidazole modifier and dichloroalkane in xylene and mixing them evenly, heating to 80°C and stirring continuously for 2 hours to obtain a chloroimidazole ionic liquid, recorded as Cl-IL; S5. Put the ZIF67-MHNT, the Cl-IL and the red poplar essential oil 2 into xylene and mix them evenly. Heat to 80° C. and continue stirring for 6 hours to obtain an adsorption material for adsorbing the red poplar essential oil, which is recorded as IL-ZIF67-MHNT.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the halloysite powder to Fe(NO3)3·9H2O in S1 is 1:0.1-10.

6. The preparation method according to claim 4, characterized in that: The mass ratio of MHNT, silanization reagent, imidazole modifier, triethylamine and maple essential oil 1 in S2 is 1:1-5:2-7:0.2-1:2-7.

7. The preparation method according to claim 4, characterized in that: The mass ratio of Im-MHNT, Zn(NO3)2·6H2O and methanol in S3 is 1:0.2-2:30-80.

8. The preparation method according to claim 4, characterized in that: The mass ratio of the imidazole modifier and the dichloroalkane in S4 is 1:0.5-3.

9. The preparation method according to claim 4, characterized in that: The mass ratio of ZIF67-MHNT, Cl-IL and Acer truncatum essential oil 2 described in S5 is 1:0.17-0.95:1-10.

10. Use of the adsorption material according to any one of claims 1 to 3 in adsorbing Pteris crenata essential oil.

Citation Information

Cited By

  • Molecularly imprinted ratio-type working electrode for detecting mitomycin C as well as preparation method and application of molecularly imprinted ratio-type working electrode

    CN120741580A